An Efficient Multi‐hop Broadcast Protocol for Emergency Messages Dissemination in VANETs. Issue 3 (1st May 2017) - Wu, Libing; Nie, Lei; Fan, Jing; He, Yanxiang; Liu, Qin; Wu, Dan
Abstract : Black‐burst based multi‐hop broadcast protocols are effective means to disseminate Emergency messages (EMs) in Vehicular ad hoc networks (VANETs). However, Clear to broadcast (CTB) collision will happen and reduce propagation speed. Aiming at this problem, we propose a Black‐burst and multi‐channel based multihop broadcast (BMMB) protocol. Vehicles with multiple antennas can transmit and sense black‐burst at different channels simultaneously based on multi‐channel technology. Compared with existing black‐burst based methods, BMMB shortens the iterative procedure to find out the optimal segment. Only one relay vehicle can be rapidly selected within the optimal segment without CTB collision. BMMB enables alternative broadcast methods, i.e., unidirectional broadcast and multi‐directional broadcast for straight roads and intersections respectively. Theoretical analysis is done for performance evaluation of BMMB, and simulation results demonstrate that BMMB performs better in terms of average one‐hop delay and propagation speed.